ER remodeling by the large GTPase atlastin promotes vacuolar growth of Legionella pneumophila. (23rd August 2017) - Steiner, Bernhard; Swart, Anna Leoni; Welin, Amanda; Weber, Stephen; Personnic, Nicolas; Kaech, Andres; Freyre, Christophe; Ziegler, Urs; Klemm, Robin W; Hilbi, Hubert
Abstract: The pathogenic bacterium Legionella pneumophila replicates in host cells within a distinct ER‐associated compartment termed the Legionella ‐containing vacuole (LCV). How the dynamic ER network contributes to pathogen proliferation within the nascent LCV remains elusive. A proteomic analysis of purified LCVs identified the ER tubule‐resident large GTPase atlastin3 (Atl3, yeast Sey1p) and the reticulon protein Rtn4 as conserved LCV host components. Here, we report that Sey1/Atl3 and Rtn4 localize to early LCVs and are critical for pathogen vacuole formation. Sey1 overproduction promotes intracellular growth of L. pneumophila, whereas a catalytically inactive, dominant‐negative GTPase mutant protein, or Atl3 depletion, restricts pathogen replication and impairs LCV maturation. Sey1 is not required for initial recruitment of ER to PtdIns(4) P ‐positive LCVs but for subsequent pathogen vacuole expansion. GTP (but not GDP) catalyzes the Sey1‐dependent aggregation of purified, ER‐positive LCVs in vitro . Thus, Sey1/Atl3‐dependent ER remodeling contributes to LCV maturation and intracellular replication of L. pneumophila . Synopsis: The intracellular pathogen Legionella pneumophila replicates within a distinct ER‐associated compartment, the Legionella ‐containing vacuole (LCV). The large, dynamin‐like GTPase atlastin3/Sey1 contributes to LCV maturation and growth by promoting ER tubule dynamics and organelle remodeling. The ER tubule‐resident large GTPase Atlastin3/Sey1 localizes to LCVs and enhances intracellular replication of L. pneumophila . Sey1 is dispensable for initial recruitment of ER to PtdIns(4) P ‐positive LCVs but promotes subsequent pathogen vacuole expansion. GTP (but not GDP) triggers the Sey1‐dependent aggregation of purified, ER‐positive LCVs in vitro . Abstract : The intracellular pathogen Legionella pneumophila replicates within a distinct ER‐associated compartment, the Legionella ‐containing vacuole (LCV). The large, dynamin‐like GTPase atlastin3/Sey1 contributes to LCV maturation and growth by promoting ER tubule dynamics and organelle remodeling.